Do operational risks and credit risks make banks more aggressive to avoid taxes? Empirical study of banking companies on the Indonesia stock exchange - Muhammad Shohihul Wahyu Muzakki; Nafis Dwi Kartiko; Lazuardi Widyanto Pratama (Directorate General of Taxes, 2023)
This study aims to analyze the relationship between credit risk and operational risk on tax avoidance aggressiveness in banking companies in Indonesia for the period 2004-2021. The total observations in the study amounted to 271 samples. The testing method in this study uses multiple regression analysis with panel data. In general, the results show that Non-Performing Loans (NPL) is positively related to to Effective Tax Rates (ETR); in this case, an increase in NPL does not make companies more aggressive in tax avoidance. While Business Operating Profitability (BOPO) is negatively related ETR, in this case, an increase in BOPO makes the company more aggressive in tax avoidance. The results show significant differences in the effect of NPL and BOPO on ETR as a proxy for tax avoidance aggressiveness between the models analyzed. Although NPL shows a significant positive relationship with ETR in one of the first models, the relationship is not significant in the other models. Meanwhile, BOPO has an insignificant negative relationship with ETR in the first model but a negative significant relationship in the second model.